Effects of the group leadership promotion approach on students' higher order thinking awareness and online interactive behavioral patterns in a blended learning environment. Issue 2 (17th February 2020) - Cheng, Shu-Chen; Hwang, Gwo-Jen; Lai, Chiu-Lin
ABSTRACT: The present study aims to incorporate a group leadership promotion approach into collaborative learning tasks in the hope of developing students' creativity, problem-solving, and critical thinking. In order to evaluate the effectiveness of the proposed approach, we recruited 59 cross-professional students from a university in northern Taiwan, and divided them into an experimental group (6 sub-groups) and a control group (6 sub-groups). The experimental group students learned with the group leadership promotion approach, while the control group learned with conventional blended learning approach. The results show that the students could better develop their creativity, problem-solving, critical thinking, and learning achievement via the group leadership promotion approach. Lastly, sequential analysis of their behaviors indicated that students' interaction with group leadership in online collaborative learning can promote many more creative ideas and comments, enhance reaching a consensus and making conclusions, and finally, facilitate completion of the group learning tasks.